499 The effects of disease on growth efficiency and carcass composition of beef cattle. (7th December 2018) - Maxwell, C; Hagenmaier, J; Betts, N; Rutten-Ramos, S
Abstract: Recent data suggest morbidity and mortality are increasing in feedlot cattle, primarily due to bovine respiratory disease. It is well documented that disease challenges in beef cattle result in reduced gain, efficiency and HCW in cattle fed to the same DOF. Typically, diseased animals produce carcasses with less desirable quality grades due to reduced marbling scores. More recent data suggest that although diseased animals can be fed to similar fat-thickness endpoints with added DOF, carcass weights and marbling scores are still reduced compared to non-treated contemporaries. Of note, non-treated animals with lung lesions also showed marked reductions in performance, indicating subclinical disease. While the bovine immune response to infectious disease challenge is complex, the acute inflammatory response typically results in the production of acute phase proteins and pro-inflammatory cytokines from the liver. New data suggest that respiratory disease in cattle, as indicated by lung palpation at slaughter, could be related to the presence of 1 or more liver abscesses. Disease increases the animal's maintenance energy requirements, resulting in less energy available for growth, increased production costs and lower gross revenue. Today, the majority of fed cattle are marketed on a carcass basis (grid or dressed), with HCW accounting for over 80% of the variation in gross revenue from individual animals. These economic factors make disease, and more specifically bovine respiratory disease, a costly challenge for beef production. The objective of this paper is to review the impacts of disease on growth and carcass characteristics, evaluate a large population database to evaluate trends in commercial production, and highlight potential relationships between other diseases experienced in feedlot beef production.